+0  
 
0
57
2
avatar+230 

Let A,B  be the points on the coordinate plane with coordinates  \((t-4,-1)\) and\((-2,t+3)\)   , respectively. The square of the distance between the midpoint of \(\overline{AB}\)  and an endpoint of \(\overline{AB}\)  is equal to \(t^2/2\)  . What is the value of \(t\) ?

ant101  Jul 27, 2017
Sort: 

2+0 Answers

 #1
avatar+4155 
+2

midpoint of AB  \(=\,(\frac{t-4+-2}{2}\,,\,\frac{-1+t+3}{2})\,=\,(\frac{t-6}{2}\,,\,\frac{t+2}{2})\)

 

 

an endpoint of AB  \(=\,(t-4,-1)\)

 

distance between midpoint and an endpoint  \(=\,\ \,\sqrt{(t-4-\frac{t-6}{2})^2+(-1-\frac{t+2}{2})^2}\)

 

 

\(\begin{array} \ {(t-4-\frac{t-6}{2})^2+(-1-\frac{t+2}{2})^2}\,&=&\,\frac{t^2}{2} \\~\\ {(\frac{2t}{2}-\frac{8}{2}-\frac{t-6}{2})^2+(-\frac{2}{2}-\frac{t+2}{2})^2}\,&=&\,\frac{t^2}{2} \\~\\ {(\frac{2t-8-t+6}{2})^2+(\frac{-2-t-2}{2})^2}\,&=&\,\frac{t^2}{2} \\~\\ {(\frac{t-2}{2})^2+(\frac{-t-4}{2})^2}\,&=&\,\frac{t^2}{2} \\~\\ {(\frac{t-2}{2})(\frac{t-2}2)+(\frac{-t-4}{2})(\frac{-t-4}{2})}\,&=&\,\frac{t^2}{2} \\~\\ {\frac{t^2-4t+4}{4}+\frac{t^2+8t+16}{4}} \,&=&\,\frac{t^2}{2} \\~\\ {\frac{2t^2+4t+20}{4}}\,&=&\,\frac{t^2}{2} \\~\\ 2t^2+4t+20 \,&=&\,2t^2 \\~\\ 4t+20\,&=&\,0 \\~\\ 4t\,&=&\,-20 \\~\\ t\,&=&\,-5 \end{array}\)

hectictar  Jul 27, 2017
edited by hectictar  Jul 27, 2017
 #2
avatar+18369 
+2

Let A,B  be the points on the coordinate plane with coordinates \(\tbinom{t-4}{-1}\)  and \(\tbinom{-2}{t+3}\), respectively.
The square of the distance between the midpoint of  \( \overline{AB}\) and an endpoint of   \(\overline{AB}\) is equal to  \(\tfrac{t^2}{2}\).
What is the value of \(t\) ?

 

\(\begin{array}{|rcll|} \hline \left ( \frac{ \overline{AB} } {2} \right)^2 &=& \frac{t^2}{2} \\ \frac{ \overline{AB}^2 } {4} &=& \frac{t^2}{2} \\ \mathbf{ \overline{AB}^2 } & \mathbf{=} & \mathbf{2 t^2 } \\ \hline \end{array} \)

 

\(\begin{array}{|rcll|} \hline \overline{AB}^2 &=& [~ (t-4)-(-2) ~ ]^2 + [~ (-1) - (t+3) ~ ]^2 \\ \overline{AB}^2 &=& (~ t-4+2 ~)^2 + (~ -1 - t -3 ~ )^2 \\ \overline{AB}^2 &=& (~ t-2 ~)^2 + (~ - t -4 ~ )^2 \\ \overline{AB}^2 &=& (~ t-2 ~)^2 + [~ - (t +4) ~ ]^2 \\ \overline{AB}^2 &=& (~ t-2 ~)^2 + (~ t +4 ~)^2 \quad & | \quad \overline{AB}^2 = 2t^2\\ 2t^2 &=& (~ t-2 ~)^2 + (~ t +4 ~)^2 \\ 2t^2 &=& t^2 -4t + 4 + t^2 + 8t + 16 \\ 0 &=& -4t + 4 + 8t + 16 \\ 0 &=& 4t + 20 \\ 4t &= -20 \\ t &=& -\frac{20}{4} \\ \mathbf{ t } & \mathbf{=} & \mathbf{-5} \\ \hline \end{array}\)

 

 

laugh

heureka  Jul 27, 2017
edited by heureka  Jul 27, 2017

3 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details